2022
DOI: 10.1177/2632010x221096378
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Classification of Gastric Cancer With Emphasis on PDL-1 Expression: The First Report From Iran

Abstract: Background: Gastric cancer is one of the lethal cancers and there is no effective treatment for these patients and still, 5-year survival rate is about 25% to 30%. Finding reliable biomarkers for early-stage diagnosis, targeted therapy, and survival prediction is a priority in this cancer. Objectives: In this study we were trying to know about the molecular classification of gastric cancers in a group of patients from the South of Iran. Patients and Methods: In a cross sectional study, 50 specimens of gastric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Molecular classification might increase the complexity and costs of diagnosis; however, it provides valuable information necessary to select targeted treatment that may increase the survival of gastric cancer patients [23,24].…”
Section: Molecular Subtypes In Gastric Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular classification might increase the complexity and costs of diagnosis; however, it provides valuable information necessary to select targeted treatment that may increase the survival of gastric cancer patients [23,24].…”
Section: Molecular Subtypes In Gastric Cancermentioning
confidence: 99%
“…In gastric cancer, PD-L1 CPS ≥ 1 generally defines PD-L1-positive tumors [62]. Some studies have reported significantly higher PD-L1 expression rates in HER2negative tumors [24,63], while other studies reported opposite findings [64,65] or found no differences in PD-L1 expression between HER2-positive and negative tumors [7,66]. These discrepancies may be due to the heterogeneity of the populations studied, differences in the scoring methods, or in the monoclonal antibodies used for detection.…”
Section: Pd-l1 Expression In Her2-positive Gastric Cancermentioning
confidence: 99%
“…Molecular classification might increase the complexity and costs of diagnosis, however, it provides valuable information necessary to select targeted treatment that may increase the survival of gastric cancer patients [7,8].…”
Section: Molecular Subtypes In Gastric Cancermentioning
confidence: 99%
“…In gastric cancer, PD-L1 CPS ≥ 1 generally defines PD-L1-positive tumors [41]. Some studies have reported significantly higher PD-L1 expression rates in HER2negative tumors [8,42], while other studies reported opposite findings [43,44] or found no differences in PD-L1 expression between HER2-positive and negative tumors [7,45]. These discrepancies may be due to the heterogeneity of the populations studied, differences in the scoring methods, or in the monoclonal antibodies used for detection.…”
Section: Pd-l1 Expression In Her2-positive Gastric Cancermentioning
confidence: 99%